Drugs and sport. Research findings and limitations - Clarkson, P. M.; Thompson, H. S. (Sports Medicine, 1997)
Many types of drugs are used by athletes to improve performance. This paper reviews the literature on 3 categories of drugs: those that enhance performance as stimulants (amphetamines, ephedrine, and cocaine), those that are used to reduce tremor and heart rate (beta-blockers) and those involved in bodyweight gain or loss (anabolic-androgenic steroids, growth hormone, beta 2-agonists, and diuretics). Limitations of research on these drugs as they relate to performance enhancement are also discussed. The numerous studies that have assessed the effects of amphetamines on performance report equivocal results. This may be ue to the large interindividual variability in the response to the drug and the small sample sizes used. Most studies, however, show that some individuals do improve exercise performance when taking amphetamines, which may be attributed to their role in masking fatigue. As a stimulant, ephedrine has not been found to improve performance in the few studies available. More recently, ephedrine has been purported to be effective as a fat burner and used by athletes to maintain or improve muscle mass. Although research on individuals with obesity supports the use of ephedrine for fat loss, no studies have been done on athletes. The few studies of cocaine and exercise suggest that little to no performance gains are incurred from cocaine use. Moreover, the sense of euphoria may provide the illusion of better performance when, in actuality, performance was not improved or was impaired. beta-Blockers have been found to reduce heart rate and tremor and to improve performance in sports that are not physiologically challenging but require accuracy (e.g. pistol shooting). However, there is evidence that some individuals may be high responders to beta-blockers to the extent that their heart rate response is so blunted as to impair performance. Although equivocal, several studies have reported that anabolic-androgenic steroids increase muscle size and strength. However, most studies are not well controlled and use insufficient drug doses. One recent well controlled study did find an increase in muscle mass and strength with supraphysiological doses, and the improvements were greater in participants who were also resistance training. There is little information available on the effects of growth hormone on muscle mass or performance in athletes, although data suggest that growth hormone administration does not increase muscle protein synthesis. beta 2-Agonists, such as clenbuterol and salbutamol, when administered orally appear to improve muscular strength due to their potential role in increasing muscle mass. However, studies have not been done using athletes. Diuretics results in a loss of body water and hence bodyweight that can be advantageous for sports with strict bodyweight classifications. There is insufficient evidence on possible performance decrements in the field that could result from dehydration induced by the diuretics. Overall, the most significant concern in studies of drug use is the large inter-individual variability in responses to a drug. Further studies are needed to understand why some individuals are more responsive than others and to assess whether the responses are consistent for a given individual. Most studies of drug effectiveness have not used athletes. The effectiveness of many drugs may be reduced in highly trained athletes because there is a lower margin for improvement.